2015
DOI: 10.2480/agrmet.d-15-00008
|View full text |Cite
|
Sign up to set email alerts
|

Panicle emergence pattern and grain yield of rice plants in response to high temperature stress

Abstract: The timing of panicle emergence in rice (Oryza sativa L.) is an important trait. We studied the effects of increasing temperatures during growing seasons on the emergence of first panicle, consequent emerging panicle numbers, and grain yields in rice plant using temperature gradient chambers (TGCs) located in a part of Japan with a humid subtropical climate. Four japonica varieties, Koshihikari, Akitakomachi, Hitomebore, and Nipponbare, were exposed to different temperatures in the TGCs. The number of days fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, the occurrence of sterility may influence on the source-sink balance, which leads to compensatory effects, such as changing the grain size distribution. It has been also reported that the late-emerging panicles can compensate for the failure to fertility of the early-emerging panicles, resulting in no reduction of the yield (e.g., Maruyama et al, 2015). Conversely, this means that even if HISS increases due to global warming and the resulting increasingly frequent heat waves, its effects on rice yield would not be directly detected by yield monitoring such as the monitoring that is done under Japan's national Crop Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the occurrence of sterility may influence on the source-sink balance, which leads to compensatory effects, such as changing the grain size distribution. It has been also reported that the late-emerging panicles can compensate for the failure to fertility of the early-emerging panicles, resulting in no reduction of the yield (e.g., Maruyama et al, 2015). Conversely, this means that even if HISS increases due to global warming and the resulting increasingly frequent heat waves, its effects on rice yield would not be directly detected by yield monitoring such as the monitoring that is done under Japan's national Crop Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that if a Takanari‐like rice variety was cultivated under approximate [CO 2 ] in 2050 (200 μmol/mol over present‐day [CO 2 ]), we could feasibly maintain the cost for water at the same level as for cultivating common cultivars like Koshihikari at current [CO 2 ]. Even if air temperature increased alongside [CO 2 ] in the future, a 14‐day simulation of Takanari in E‐CO 2 with air temperature increased by 2°C results in an ET of 3.9 ± 1.4 mm/day, which is still approximately the same level of ET of Koshihikari in A‐CO 2 , although the simulation did not consider the temperature effects on phenology and downregulation of photosynthesis (Adachi et al., ; Maruyama et al., ).…”
Section: Discussionmentioning
confidence: 99%